PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L. Wilczeck) YANG DIPUPUK N DENGAN DOSIS BERBEDA DAN PENYIANGAN - Rusmana . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
The research was conducted to know the effect of different doses of nitrogen fertilizer on the land without and with weeding. The experiments used Randomized Completely Block Design as Factorial was conducted at Sitandu Curug Serang. The result showed that the difference of dosage of N fertilizer up to 100 kg Urea ha-1 did not show the difference of green bean plant yield. Weeding once a week could increase the yield and the components of green beans about 78.3% both the number of pods per plant and the weight of seeds per plant.Keywords: Green bean, Nitrogen, Weeding